2017
DOI: 10.13075/ijomeh.1896.01073
|View full text |Cite
|
Sign up to set email alerts
|

Influenece of the CPRmeter on angular position of elbows and generated forces during cardiopulmonary resuscitation

Abstract: Objectives: It is commonly known that ergonomics in emergency medical services (EMS) is very important. Emergency medical services workers are exposed to different conditions and they should perform a variety of tasks. Material and Methods: The aim of the work has been to analyze the angular position of elbows and forces generated by the upper limbs during cardiopulmonary resuscitation with and without the CPRmeter based on feedback technology. Ten male paramedics and 10 male non-paramedics, in a kneeling posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…A CPRmeter is a device which gives real-time feedback related to the depth and rate of chest wall movement during compression and detects whether the patient's chest is able to fully recoil between compressions. Some studies evaluating the CPRmeter showed stability of force applied after 4 min of CPR or greater and optimization of positioning with improvement in compression depth and rate, however, additional studies suggest that compression quality was inferior to standard CPR and there were delays in initiation of CPR [17,22,23]. One study looked at the accuracy of placement of a "CPR Assist" feedback device by medical personnel and found that approximately half of the time the device was in an inappropriate position on the chest, increasing the risk of sternal and rib fractures [24].…”
Section: Real-time Feedback Devicesmentioning
confidence: 99%
“…A CPRmeter is a device which gives real-time feedback related to the depth and rate of chest wall movement during compression and detects whether the patient's chest is able to fully recoil between compressions. Some studies evaluating the CPRmeter showed stability of force applied after 4 min of CPR or greater and optimization of positioning with improvement in compression depth and rate, however, additional studies suggest that compression quality was inferior to standard CPR and there were delays in initiation of CPR [17,22,23]. One study looked at the accuracy of placement of a "CPR Assist" feedback device by medical personnel and found that approximately half of the time the device was in an inappropriate position on the chest, increasing the risk of sternal and rib fractures [24].…”
Section: Real-time Feedback Devicesmentioning
confidence: 99%